Tissue- and transformation-specific phosphotyrosyl proteins in v-erbB-transformed cells. - McManus, M J (1995)
To understand the mechanism of tissue-specific and transformation-specific signaling by the v-ErbB oncoprotein, we have investigated signaling pathways downstream of this transmembrane tyrosine kinase. In this report, we describe tissue-specific patterns of phosphotyrosyl proteins in three distinct cell types transformed by the v-erbB oncogene: fibroblasts, erythroblasts, and endothelial cells. In addition, we describe transformation-specific tyrosine phosphorylation events and signal complex formation in v-erbB-transformed fibroblasts. Two patterns of phosphotyrosyl proteins have been detected in v-erbB-transformed cells. The first is a fibroblast-specific pattern which includes unique phosphotyrosyl proteins of 170 kDa (c-ErbB1), 158 kDa, and 120 kDa (the catenin-like protein p120cas). The second is an erythroblast/endothelial cell-specific pattern which includes a prominent unidentified phosphotyrosyl protein of 120 kDa. Evaluation of the phosphotyrosyl proteins p120cas and SHC in chicken embryo fibroblasts infected with transforming and nontransforming v-erbB mutants reveals transformation-specific patterns of tyrosine phosphorylation. One corollary of these phosphorylation events in v-erbB-transformed fibroblasts is the formation of a complex involving SHC, growth factor receptor-bound protein 2, and a novel 75-kDa phosphotyrosyl protein. The results of these studies suggest that the v-ErbB oncoprotein can couple to multiple signal transduction pathways, that these pathways are tissue specific, and that v-erbB-mediated transformation involves specific tyrosine phosphorylation events.